Thymol, a constituent of thyme essential oil, is a positive allosteric modulator of human GABA A receptors and a homo‐oligomeric GABA receptor from Drosophila melanogaster - Priestley, Caroline M; Williamson, Elizabeth M; Wafford, Keith A; Sattelle, David B (British journal of pharmacology, 2003)
The GABA‐modulating and GABA‐mimetic activities of the monoterpenoid thymol were explored on human GABA A and Drosophila melanogaster homomeric RDL ac GABA receptors expressed in Xenopus laevis oocytes, voltage‐clamped at −60 mV. The site of action of thymol was also investigated. Thymol, 1–100 μ M , resulted in a dose‐dependent potentiation of the EC 20 GABA response in oocytes injected with either α 1 β 3 γ 2s GABA A subunit cDNAs or the RDL ac subunit RNA. At 100 μ M thymol, current amplitudes in response to GABA were 416±72 and 715±85% of controls, respectively. On both receptors, thymol, 100 μ M , elicited small currents in the absence of GABA. The EC 50 for GABA at α 1 β 3 γ 2s GABA A receptors was reduced by 50 μ M thymol from 15±3 to 4±1 μ M , and the Hill slope changed from 1.35±0.14 to 1.04±0.16; there was little effect on the maximum GABA response. Thymol (1–100 μ M ) potentiation of responses to EC 20 GABA for α 1 β 1 γ 2s, α 6 β 3 γ 2s and α 1 β 3 γ 2s human GABA A receptors was almost identical, arguing against actions at benzodiazepine or loreclezole sites. Neither flumazenil, 3‐hydroxymethyl‐ β ‐carboline (3‐HMC), nor 5 α ‐pregnane‐3 α , 20 α ‐diol (5 α ‐pregnanediol) affected thymol potentiation of the GABA response at α 1 β 3 γ 2s receptors, providing evidence against actions at the benzodiazepine/ β ‐carboline or steroid sites. Thymol stimulated the agonist actions of pentobarbital and propofol on α 1 β 3 γ 2s receptors, consistent with a mode of action distinct from that of either compound. These data suggest that thymol potentiates GABA A receptors through a previously unidentified binding site. British Journal of Pharmacology (2003) 140 , 1363–1372. doi: 10.1038/sj.bjp.0705542